Challenges in Indonesia's Investment Policy for Stimulating Economic Growth Through the Omnibus Law - Rilke Jeffri Huwae; Basuki Rekso Wibowo; Dedy Ardian Prasetyo (Badan Penerbit STIEPARI Press, 2024)
Indonesia encounters a multitude of obstacles in enhancing investment and fostering economic progress. Despite the significant potential of investment markets, inadequate investment regulation has emerged as a significant obstacle to achieving sustainable economic growth. The government is addressing this challenge by implementing the Omnibus Law, which seeks to streamline rules and foster an environment conducive to investment. Nevertheless, the execution of this Omnibus Law is encountering several hindrances, including discrepancies in regulations between the central and regional authorities, as well as a wide range of public responses. The study seeks to analyze the obstacles to investment policy in Indonesia and its influence on economic growth. This study employs a normative jurisprudence approach, which entails examining the provisions of the relevant legislation about capital investments and the Omnibus Law. This approach also encompasses the examination of literature and other legal materials to have a full understanding of the diverse pertinent legal facets. This normative jurisprudential approach will aid in detecting legal ambiguity, intricate bureaucracy, and diverse regulatory obstacles that impact the investment environment in Indonesia. Furthermore, the study will assess the efficacy of the Omnibus Law in streamlining rules and promoting investment. The findings of this study indicate that the primary barriers to more investment in Indonesia are the presence of legal ambiguity and a complex bureaucratic system. While the Omnibus Law holds promise for improving the investment climate, its successful implementation necessitates increased openness and public involvement. It is advisable for the Indonesian government to improve coordination between the central and regional authorities, and to engage several stakeholders in the process of policy-making. These steps are anticipated to decrease ambiguity and enhance investor assurance, hence stimulating sustainable economic expansion.